Characterization and Technological Features of Autochthonous Coagulase‐Negative Staphylococci as Potential Starters for Portuguese Dry Fermented Sausages. Issue 5 (19th April 2016) - Semedo‐Lemsaddek, Teresa; Carvalho, Laura; Tempera, Carolina; Fernandes, Maria H.; Fernandes, Maria J.; Elias, Miguel; Barreto, António S.; Fraqueza, Maria J.
Abstract: The manufacture of dry fermented sausages is an important part of the meat industry in Southern European countries. These products are usually produced in small shops from a mixture of pork, fat, salt, and condiments and are stuffed into natural casings. Meat sausages are slowly cured through spontaneous fermentation by autochthonous microbiota present in the raw materials or introduced during manufacturing. The aim of this work was to evaluate the technological and safety features of coagulase‐negative staphylococci (CNS) isolated from Portuguese dry fermented meat sausages in order to select autochthonous starters. Isolates ( n = 104) obtained from 2 small manufacturers were identified as Staphylococcus xylosus, Staphylococcus equorum, Staphylococcus saprophyticus, and Staphylococcus carnosus . Genomically diverse isolates ( n = 82) were selected for further analysis to determine the ability to produce enzymes (for example, nitrate‐reductases, proteases, lipases) and antibiotic susceptibility. Autochthonous CNS producing a wide range of enzymes and showing low antibioresistance were selected as potential starters for future use in the production of dry fermented meat sausages.